Pengaruh Suhu Awal Air dan Lama Perendaman terhadap Viabilitas dan Vigoritas Benih Bunga Gumitir (Tagetes erecta L.) - Dewi, Ni Putu Elvina Kusuma; Wijana, Gede; Darmawati, Ida Ayu Putri (Agrotrop : Journal on Agriculture Science, 2024)
The effect of the Initial Temperature of the Water and the soaking time on Viability and Vigority of Marigold Flower Seeds ( Tagetes erecta L.). Marigold is a floral ornamental plant, which is potentially marketed in Indonesia especially in Bali. Marigold is multiplied through seeds, so the quality of seeds is highly observed. An uneven flare and a low flare power can affect the growth of marigold. This research aims to find out the initial temperature, the soaking time and interaction influences the viability and vigor of the flower seed. The research began in August-October 2023, which is located at the Laboratory of Plant ?reeding and Seed Technology, Agroecology Studies Program, Faculty of Agriculture University of Udayana. This research used a Completely Randomized Factorial Design, namely the initial temperature treatment consisted of 3 levels (30?, 40?, 50?), and the soaking time consisted of 4 levels (30, 60, 90 and 120) minutes. The results of the study showed a significant interaction influencing the viability and vigor of marigold seeds, where the initial temperature of 40°C with 30 minutes of immersion is the best interaction, with germination percentage (86%), maximum potential growth rate (92%), simultaneous growth (75.33%), the percentage growth rate (11.61%/etmal) and seed vigor indeks (5199,47).